UNCOVERING THE POWER OF E-WOM: HOW GADGETIN YOUTUBE CONTENT GENERATES PURCHASE INTENTION THROUGH QUALITY AND CREDIBLE INFORMATION - Qurrotul Aini, Nurul; Prihatining Wilujeng, Ita; Siswanto, Ely (Penerbit Lafadz Jaya, 2025)
The study was conducted to assess the influence of information quality and information credibility on purchase intention, with e-WOM adoption serving as an intermediate variable. The participants in this study are comprised of GadgetIN viewers on YouTube. A sample of 165 participants was determined using the Daniel & Terrel formula and selected through purposive sampling techniques. This research falls into the category of explanatory studies, employing a quantitative approach and utilizing a Likert scale questionnaire as a tool for data collection. Statistical analysis was executed by evaluating the outer model to appraise the disseminated questionnaire’s validity and reliability, also the inner model to evaluate the model and test the hypothesis. With the assistance of the SmartPLS 4.0 application, the study found that information quality (Q) and information credibility (C) have a positive significant effect on e-WOM adoption (A). However, information quality and information credibility have not a positive significant effect on purchase intention (P). Their impact on purchase intention becomes meaningful only when filtered through the e-WOM adoption. Accordingly, this study highlights e-WOM adoption as a crucial variable that effectively shapes consumers' purchase intention.